Using ICTS for environmental awareness the case of the Baguio national high school's project - De Jesus, Ana Katrina P. (UP Los Baños Journal, 2014)
This is a case study focused on Hour Environment, the ICT project on environmental protection and preservation of the Baguio City National High School. The project is designed to integrate ICT-based activities, such as electronic poster making, digital essay writing, and animated video production, in the school curriculum. Interviews focus group discussion, and supporting documents served as bases for the case analysis. Results shows that ICT stimulates students, interest for it allows more student-centered learning. The project, spanning six months, is effective only to some extent since there was no clear, quantifiable improvement in the environmental awareness level of the students. The challenge with ICT integration in the curriculum is that, without careful instructional design by teachers, the ICT tools are limited to being mere tools, without only merit over traditional teaching aids. Teachers must structure the learning experience, guided by a well-designed lesson preparatory to the conduct of ICT-based activities. A strategic framework for environmental education is recommended. This way, the ICT project becomes a strategic and participatory program that "conveys information, builds understanding, improves skills, and enables sustainable actions" for the participants.